Pengaruh Likuiditas Dan Kecukupan Modal Terhadap Profitabilitas Pada PT. BPR Artha Bali Jaya Di Batubulan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
This study aims to analyze the effect of liquidity, measured by the Loan to Deposit Ratio (LDR), and capital adequacy, measured by the Capital Adequacy Ratio (CAR), on profitability, measured by the Return on Assets (ROA), at PT. BPR Artha Bali Jaya in Batubulan. The data used are secondary data in the form of financial statements for the period 2022-2024. The analytical method applied is multiple linear regression with classical assumption tests, including normality, multicollinearity, autocorrelation, and heteroscedasticity tests. The results indicate that, partially, LDR has a positive and significant effect on ROA, and CAR also has a positive and significant effect on ROA. Simultaneously, LDR and CAR significantly influence ROA, with an adjusted R² value of 0.741, meaning that 74.1% of ROA variation can be explained by these two variables, while the remaining 25.9% is influenced by other factors outside this study. These findings suggest that optimal management of liquidity and capital can enhance the profitability of PT. BPR Artha BaliJaya.